O016 Actigraphy: A review of practice down under. (9th November 2022) - Pham, H; Saunders, T; Vandeleur, M
Abstract: Background: In 2018, the American Academy of Sleep Medicine (AASM) published practice guidelines for use of actigraphy in evaluating adult and paediatric patients with suspected sleep disorders. Whilst there is significant evidence of actigraphy use in research, this study aims to evaluate current and future intended use of actigraphy in paediatric clinical cohorts across Australia and New Zealand (NZ). Methods: A 16-item survey was electronically distributed to medical leads from Australian and NZ paediatric sleep centres. Questions enquired on sleep centre logistics, current actigraphy practice behaviours and qualitative assessments on future use. Progress to date: The survey was distributed on July 22nd. Thus far, 8 responses have been returned, representing a range of locales, centre types and actigraphy practices. Findings will be collated and presented. Intended outcome and impact: This study will provide an understanding for the contemporary trends in actigraphy use through Australia and NZ. This is particularly relevant given changes across recent years with both an increase in commercial prevalence for consumer sleep health devices as well as a surge in ambulatory medical services following the COVID-19 pandemic. It will identify barriers limiting its universal utility and explore clinician preferences for future practice. Such findings can guide actions around improving clinical services, product design and government funding advocacy.